1998
DOI: 10.1139/cjc-76-11-1654
|View full text |Cite
|
Sign up to set email alerts
|

The self-assembly of a layered material: metal-alkanethiolate bilayers

Abstract: /npsi/ctrl?action=rtdoc&an=8894811&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=8894811&lang=frAccess and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…These structures have been observed to extend laterally for a length of 60−70 alkanethiols . Similar structures have been formed at the interface of an organic phase, containing thiol, and an aqueous phase, containing silver or copper ions . Such structures would be consistent with our observations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These structures have been observed to extend laterally for a length of 60−70 alkanethiols . Similar structures have been formed at the interface of an organic phase, containing thiol, and an aqueous phase, containing silver or copper ions . Such structures would be consistent with our observations.…”
Section: Resultssupporting
confidence: 91%
“…These data are not consistent with the model of alkanethiol monolayers covering mounds of gold oxide on the gold surface as proposed by Ron et al Our data instead indicate that the islands are an insoluable complex primarily composed of a bilayer of the corresponding thiol. Our data are consistent with the complex being the gold−thiolate analogue to silver−thiolate and copper−thiolate complexes previously observed by others. ,, …”
Section: Discussionsupporting
confidence: 93%
“…Figure a shows the TEM image of the copper dithiolate precursor. The filmlike morphology indicates that the precursor has a layered structure, which is similar to the layered structure of the copper thiolate polymers . In Figure b−d, TEM images of Cu 2 S nanocrystals synthesized at 185 °C reveal the shape evolution from small spherical particles into flat disks with increased reaction time.…”
mentioning
confidence: 67%
“…These SAMs have been intensively studied and are of great interest due to the unique properties of the resulting surfaces, including stabilization and passivation to electrochemistry and other reactions. While much of the study of copper/thiol chemistry has been restricted to the formation and properties of SAMs, it has been shown that multilayers can form into independent lamellar structures ( Figure 1 ) [ 10 21 ]. It was discovered in this study that under the right conditions, these types of layered compounds can be formed in a sulphur guard bed at elevated temperature and pressure, and in the presence of a hydrocarbon solvent.…”
Section: Introductionmentioning
confidence: 99%